2016
DOI: 10.1002/2016jg003422
|View full text |Cite
|
Sign up to set email alerts
|

Does mycorrhizal inoculation improve plant survival, aggregate stability, and fine root development on a coarse‐grained soil in an alpine eco‐engineering field experiment?

Abstract: Steep vegetation‐free talus slopes in high mountain environments are prone to superficial slope failures and surface erosion. Eco‐engineering measures can reduce slope instabilities and thus contribute to risk mitigation. In a field experiment, we established mycorrhizal and nonmycorrhizal research plots and determined their biophysical contribution to small‐scale soil fixation. Mycorrhizal inoculation impact on plant survival, aggregate stability, and fine root development was analyzed. Here we present plant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 57 publications
0
8
0
1
Order By: Relevance
“…As they are relatively easy to assess, Root Mass Density (RMD = root dry mass per soil volume) and Root Length Density (RLD = root length per soil volume) are normally used in studies dealing with hillslope stability (Pohl et al 2012;Erktan et al 2015;Hudek et al 2017b). However, in alpine habitats, there are only few studies dealing with roots, and even less is known about their role in maintaining ecosystem services above the timberline (Bast et al 2016;Hudek et al 2017a, b;Pohl et al 2009Pohl et al , 2011.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As they are relatively easy to assess, Root Mass Density (RMD = root dry mass per soil volume) and Root Length Density (RLD = root length per soil volume) are normally used in studies dealing with hillslope stability (Pohl et al 2012;Erktan et al 2015;Hudek et al 2017b). However, in alpine habitats, there are only few studies dealing with roots, and even less is known about their role in maintaining ecosystem services above the timberline (Bast et al 2016;Hudek et al 2017a, b;Pohl et al 2009Pohl et al , 2011.…”
Section: Introductionmentioning
confidence: 99%
“…The most relevant previous studies dealing with the impact of vegetation dynamics on hillslope functioning above the timberline have mainly dealt with narrow environmental gradients (Bast et al 2014(Bast et al , 2016Martin et al 2010;Pohl et al 2009Pohl et al , 2012. Therefore, little is known about the long-term development of hillslope stability during landscape evolution.…”
Section: Introductionmentioning
confidence: 99%
“…Biotic factors play a key role in soil stability, and fungal hyphae, especially those produced by arbuscular mycorrhizal fungi (AMF), are among the most important factors affecting long-term soil aggregation [5,[15][16][17][18][19][20][21][22]. Much of the aggregating capacity of fungi is attributed to their filamentous growth habit giving the ability to enmesh particles in soil [5,23].…”
Section: Introductionmentioning
confidence: 99%
“…For the last 30 years, practitioners and scientists have been studying the installation phase, by e.g. examining the relationship between the richness of pioneer species and soil aggregate stability (Pohl et al, 2012), or the efficacy of using mycorrhizal inoculations to improve plant growth and soil structure on eroded soil (Powell, 1980;Yildiz et al, 2015;Bast et al, 2016;Demenois et al, 2017). These studies concluded that the key to fully understanding ecological processes at eroded sites requires similar long-term experiments in the field.…”
Section: Selection Of Plant Speciesmentioning
confidence: 99%